Investigation of some oleochemicals as green inhibitors on mild steel corrosion in sulfuric acid - Rafiquee M.Z.A.; Khan S.; Saxena N.; Quraishi M.A. (My University, 2025)
The inhibitive effect of four oleo chemicals (namely; 2-Pentadecyl-1,3- imidazoline (PDI), 2-Undecyl-1,3-imidazoline (UDI), 2-Heptadecyl-1,3-imidazoline (HDI), 2-Nonyl-1,3-imidazoline (NI)), regarded as green inhibitors, were studied for the corrosion protection of mild steel in 0.5 M H2SO 4. The methods employed were weight loss, potentiodynamic polarization and electrochemical impedance techniques. Scanning electron microscopy (SEM) was carried out on the inhibited and uninhibited metal samples to characterize the surface. The purity of synthesized inhibitors was checked by FT-IR and NMR studies. The inhibition efficiency increased with increase in inhibitor concentration, immersion time and decreased with increase in solution temperature. No significant change in IE values was observed with increase in acid concentration. The best performance was obtained for UDI possessing 96.2% inhibition efficiency at 500 ppm concentration. The adsorption of the compounds on the mild steel surface in the presence of sulfuric acid obeyed Langmuir's adsorption isotherm. The values obtained for free energy of adsorption and heats of adsorption suggest physical adsorption. The addition of inhibitor decreased the entropy of activation suggesting that the inhibitors are more orderly arranged along the mild steel surface. The potentiodynamic polarization data indicate mixed control. The electrochemical impedance study further confirms the formation of a protective layer on the mild steel surface through the inhibitor adsorption. © 2009 Springer Science+Business Media B.V.